2020
DOI: 10.1007/s00392-020-01775-x
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day incidence of stroke after transfemoral transcatheter aortic valve implantation: meta-analysis and mixt-treatment comparison of self-expandable versus balloon-expandable valve prostheses

Abstract: Aims Stroke is a major complication after transcatheter aortic valve implantation (TAVI). Although multifactorial, it remains unknown whether the valve deployment system itself has an impact on the incidence of early stroke. We performed a meta- and network analysis to investigate the 30-day stroke incidence of self-expandable (SEV) and balloon-expandable (BEV) valves after transfemoral TAVI. Methods and results Overall, 2723 articles were searched directly comparing the performance of SEV and BEV after trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Thirty-day stroke is a significant complication after TAVR, and its relationship with THV types remains unclear. Seppelt et al reported stroke rates of 1.8% and 3.1% at thirty days after TAVR with SEV and BEV, respectively [ 37 ]. On the contrary, our research findings revealed that the early stroke incidence rates for Evolut SEV, ACURATE SEV, and SAPIEN BEV were 3.30%, 2.60%, and 1.90%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-day stroke is a significant complication after TAVR, and its relationship with THV types remains unclear. Seppelt et al reported stroke rates of 1.8% and 3.1% at thirty days after TAVR with SEV and BEV, respectively [ 37 ]. On the contrary, our research findings revealed that the early stroke incidence rates for Evolut SEV, ACURATE SEV, and SAPIEN BEV were 3.30%, 2.60%, and 1.90%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show a higher incidence of stroke with BEV than SEV while some show similar stroke rates. 29,30 A possible explanation for the higher stroke rate with the BEV design includes rapid ventricular pacinginduced cerebral hypoperfusion during BEV deployment. 31 Post-TAVR strokes and silent brain infarcts are associated with post-procedure early cognitive decline, leading to increased mortality and morbidity.…”
Section: Favours Sevmentioning
confidence: 99%